2011
DOI: 10.3899/jrheum.110613
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-12B Genetic Polymorphism with the Susceptibility and Disease Severity of Ankylosing Spondylitis

Abstract: The IL-12B A1188C genotype was associated with the development and disease severity of AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
(33 reference statements)
4
29
1
3
Order By: Relevance
“…Consistent with these studies, the current research also showed a higher number of MMP-3 positive cells in synovial tissues from the disease group compared to the control group, and identified a significantly positive relationship between MMP-3 transcript levels and CRP or BASDAI indices. As a major body inflammatory factor, CRP can reflect the severity of AS while the BASDAI score has been widely used to directly evaluate disease progression (van der Linden et al, 1984;Wong et al, 2012). We suggest that this relationship is due to the fact that MMP-3 directly participates in the degradation of the extracellular matrix, and its elevation can activate multiple MMP factor precursors including MMP-1, -9, and -13 to further accelerate the degradation of joint cartilage matrix, destroy cartilage, and advance the progression of AS Kawamura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, the current research also showed a higher number of MMP-3 positive cells in synovial tissues from the disease group compared to the control group, and identified a significantly positive relationship between MMP-3 transcript levels and CRP or BASDAI indices. As a major body inflammatory factor, CRP can reflect the severity of AS while the BASDAI score has been widely used to directly evaluate disease progression (van der Linden et al, 1984;Wong et al, 2012). We suggest that this relationship is due to the fact that MMP-3 directly participates in the degradation of the extracellular matrix, and its elevation can activate multiple MMP factor precursors including MMP-1, -9, and -13 to further accelerate the degradation of joint cartilage matrix, destroy cartilage, and advance the progression of AS Kawamura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent GWAS have pointed out a set of polymorphisms in IL-12B gene that is consistently associated with chronic inflammatory disorders. The rs3212227 (A→C) polymorphism present in the 3'UTR region of IL-12B has been associated with psoriasis 111 , type 1 112 and type 2 diabetes mellitus 113 , multiple sclerosis 114 , ankylosing spondylitis 115 , allergic rhinitis 116 , asthma 117 , and lepromatous leprosy 118 . However, the information regarding the association of CAD with polymorphisms present in the IL-12B gene is scarce.…”
Section: Il-12b Genementioning
confidence: 99%
“…Te powiązania dotyczą przekazywania sygnału przez czynnik martwicy nowotworu (tumor necrosis factor -TNF) (loci TNFRSF1A, TRADD i TNFSF15), przekazywania sygnału i wytwarzania interleukiny (IL) 1 (polimorficzne odmiany genów IL-1R2, IL-1Ra, IL-1A, IL-1B, IL-1RN), IL-6 (polimorficzna odmiana genu IL-6 i STAT3) oraz IL-23 [13][14][15][16][17][18][19]. Interleukinę 23 tworzą dwa łańcuchy -swoisty dla niej łańcuch IL-23p19 oraz łańcuch IL-12p40, wykorzystywany także przez IL-12.…”
Section: Geny Spoza Układu Hlaunclassified
“…Interleukinę 23 tworzą dwa łańcuchy -swoisty dla niej łańcuch IL-23p19 oraz łańcuch IL-12p40, wykorzystywany także przez IL-12. Łańcuch IL-12p40 jest kodowany przez gen IL-12B, a genotyp IL-12B A1188C zwiększa 2-krotnie ryzyko rozwoju ZZSK i koreluje z klinicznie cięższym przebiegiem choroby [17]. Z ZZSK jest powiązanych również kilka polimorficznych odmian genu kodującego receptor dla IL-23 (IL-23R), przy czym warianty o obniżonej reaktywności na IL-23 są genami protekcyjnymi, a inne genami ryzyka [18,19].…”
Section: Geny Spoza Układu Hlaunclassified